Investigating Teachers' Corrective Feedback in Writing - Siti Nurhasanah; Apandi Apandi; Linda Linda (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2021)
In the English classroom writing as a communicating ideas considered to be most challenging. Students usually found many difficulty to expressing ideas or choosing the words which they will write. However, it is not the case if the teacher guided well their students with corrective feedback. The teacher as the fasilitator has important role in the fasilitating learning by guiding students and eliciting response from them. This study examined the teacher’s corrective feedback in respoding to students’ english writing in one of public senior high school in Indramayu. In this research, the data were obtained from a teacher of one of senior high school in Indramayu . This research were being analyzed descriptive qualitative method and therefore the data were being collected through documentation and interview questions. The framework undertaken is being proposed by Ellis, thus the interview question was being adapted from Thorsteinsen. The findings was found that there were three categories of feedbacks specifically, direct corrective feedback, unfocused corrective feedback and metalinguistics corrective feedback. Meanwhile, the reasons that the teacher provide different feedback startegies, teachers’ corrective feedbacks is the key to make students conscious of making mistake on writing assignments.